2008
DOI: 10.1007/s11103-008-9341-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis at the onset of aposporous apomixis in Paspalum notatum

Abstract: Apomixis is a route of asexual reproduction through seeds, that progresses in the absence of meiosis and fertilization to generate maternal clonal progenies. Gametophytic apomicts are usually polyploid and probably arose from sexual ancestors through a limited number of mutations in the female reproductive pathway. A differential display analysis was carried out on immature inflorescences of sexual and apomictic tetraploid genotypes of Paspalum notatum, in order to identify genes associated with the emergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(153 citation statements)
references
References 30 publications
5
145
0
Order By: Relevance
“…The proportion of polymorphic bands associated with the reproductive mode in inflorescences was relatively low (0.71%). These results agree with previous reports on the aposporous apomictic grass P. notatum [44], where a similar percentage (1.2%) of differentially expressed genes associated with apospory in premeiotic inflorescences was detected using DD. Therefore, the number of genes displaying altered expression in flowers during apomictic development shows a similar order of magnitude for aposporous and diplosporous apomixis.…”
Section: Gene Expression In Flowers and Leavessupporting
confidence: 92%
See 2 more Smart Citations
“…The proportion of polymorphic bands associated with the reproductive mode in inflorescences was relatively low (0.71%). These results agree with previous reports on the aposporous apomictic grass P. notatum [44], where a similar percentage (1.2%) of differentially expressed genes associated with apospory in premeiotic inflorescences was detected using DD. Therefore, the number of genes displaying altered expression in flowers during apomictic development shows a similar order of magnitude for aposporous and diplosporous apomixis.…”
Section: Gene Expression In Flowers and Leavessupporting
confidence: 92%
“…Sequences with similar annotations have been reported to be associated with apomixis and/or polyploidy for various other species, including Poa pratensis [53], Paspalum notatum [44,45], potato [54], Pennisetum squamulatum and Cenchrus ciliare [25], Panicum maximum [55], and Paspalum simplex [24,56]. Taking into account our previous results in E. curvula [32,33,35], the results of the present study, and those reported for other species by other authors, there are many commonalities among the different species with respect to apomixis.…”
Section: Validation Of Gene Expression By Real-time Pcrmentioning
confidence: 80%
See 1 more Smart Citation
“…This approach is complicated by the nature of asexual reproduction that prevents the generation of isogenic lines that differ solely with regard to reproductive mode. Nevertheless, transcriptome comparisons between apomictic and closely related sexual individuals from reproductive tissues at different developmental stages have uncovered pathways potentially central to apomixis including protein degradation, transcription, stress response, and cell-to-cell signaling (Albertini et al 2005;Laspina et al 2008;Sharbel et al 2010;Silveira et al 2012;Okada et al 2013).…”
Section: Differentially Expressed Genes Associated With Apomixismentioning
confidence: 99%
“…To date, plant genetic transformation has not been explored as a tool to facilitate harnessing apomixis for the benefit of agriculture. While in the past few years dozens of genes differentially expressed during sexual and apomictic development Chen et al 1999;Albertini et al 2004;Cervigni et al 2008;Laspina et al 2008) or positionally linked to apomixis (Calderini et al 2006;Conner et al 2008;Podio et al 2012) have been identified, functional studies have been performed only on randomly generated mutants originated from model sexual species.…”
Section: Introductionmentioning
confidence: 99%